2016
DOI: 10.17925/usor.2016.09.02.107
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Enhancement Rates in Laser Vision Correction

Abstract: I ntroduction:The design of the study was to look consecutively at what are the prime influences on enhancements in laser vision correction related to the perioperative environment. Methods: A prospective consecutive series of 4,079 cases was reviewed from a single surgeon at a single surgical site. Patients were followed prospectively and were only included after at least two years of postoperative follow-up. Results: The series ranged in primary treatments of spherical equivalents (SE) from 0 to -12 diopters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Also, in a single series with a single surgeon performing refractive surgery (KGS/N-78075) there have been zero reported cases of infection of which an aggressive treatment of eyelid margin disease is included. Stonecipher., et al reported the second most common reason influencing the risk of an enhancement after laser vision correction is dry eye disease [12].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in a single series with a single surgeon performing refractive surgery (KGS/N-78075) there have been zero reported cases of infection of which an aggressive treatment of eyelid margin disease is included. Stonecipher., et al reported the second most common reason influencing the risk of an enhancement after laser vision correction is dry eye disease [12].…”
Section: Introductionmentioning
confidence: 99%